Mitochondria localization induced self-assembly of peptide amphiphiles for cellular dysfunction - M. T. Jeena (Nature Portfolio, 2017)
Spatiotemporal control of intracellular molecular self-assembly holds promise for therapeutic applications. Here the authors develop a peptide consisting of a phenylalanine dipeptide with a mitochondrial targeting moiety to form self-assembling fibrous nanostructures within mitochondria, leading to apoptosis.